Implementations Supporting Automated Technology Transfer in MDE as a Service - Basso, Fábio Paulo; Rodrigues, Elder; Bernardino, Maicon; Werner, Claudia; Oliveira, Toacy (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2019)
Coopetition characterizes scenarios where competing firms establish collaborations for some intent. Here applies foundational studies built on software reuse and asset standards, such as for OSLC and RAS, asset platforms, smart contracts and others that are essential for promoting coopetition in the area. Our contribution is an experience report that provide foundations for technology transfer to software factory coopetition scenarios. Our goal is to characterize some coopetition approaches and tool support assisting Software Engineering (SE) tasks for technology transfer. This paper presents an experience report analyzing multi-case studies, implemented in local scenarios for coopetition, characterizing the research area with a summary of the main findings. The presented results are twofold: 1) With the current tool support in the state-of-the art, automation of SE tasks for technology transfer is feasible to local scenarios; and 2) However, global coopetition scenarios impose new implementation barriers.